(untitled) (Texas Journal of Engineering and Technology, 2022)
At the Gazli Gas Processing Plant, the process of purification of gases from acidic components with metildietanolamin solution leads to the occurrence of corrosion in technological systems. It was therefore tested by gravimetric methods with an anticorrosion inhibitor at a temperature of 120 0C and several different concentrations, and inhibition technology was proposed.